2006
DOI: 10.1191/135248506ms1250oa
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of multidisciplinary rehabilitation in stable multiple sclerosis patients

Abstract: Although the study was underpowered, the negative outcome exposes the difficulties in quantitative analyses of the efficacy of multidisciplinary rehabilitation, which is liable to confounding factors such as variation in the indication for treatment, in the placebo effect, and in the reliability and responsiveness of the outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 21 publications
3
41
1
2
Order By: Relevance
“…2,3 Motor and cognitive impairment, fatigue, depression, pain, incontinence, sexual dysfunction, and the unpredictability of the disease reduce health-related quality of life [4][5][6][7][8][9][10][11] and participation in work and life. 2,12,13 Although it has been difficult to show the effect of multidisciplinary rehabilitation stays in clinical trials, 14,15 several studies have suggested a positive effect of multidisciplinary rehabilitation on disability [15][16][17][18][19][20][21] and aspects of health-related quality of life. 15,17,18,20,21 A review by Khan et al 15 concluded that there was strong evidence that inpatient or outpatient rehabilitation can increase activity and participation in society, despite a lack of reduction in actual impairment.…”
mentioning
confidence: 99%
“…2,3 Motor and cognitive impairment, fatigue, depression, pain, incontinence, sexual dysfunction, and the unpredictability of the disease reduce health-related quality of life [4][5][6][7][8][9][10][11] and participation in work and life. 2,12,13 Although it has been difficult to show the effect of multidisciplinary rehabilitation stays in clinical trials, 14,15 several studies have suggested a positive effect of multidisciplinary rehabilitation on disability [15][16][17][18][19][20][21] and aspects of health-related quality of life. 15,17,18,20,21 A review by Khan et al 15 concluded that there was strong evidence that inpatient or outpatient rehabilitation can increase activity and participation in society, despite a lack of reduction in actual impairment.…”
mentioning
confidence: 99%
“…In previous rehabilitation trials in MS, failure to implement such a strategy has been held responsible for the lack of positive findings in spite of good quality trial design. 8 In the present study, significant improvements for some outcomes were found for both arms, which were larger in magnitude for the computer-assisted specific intervention for PASAT-2 and PASAT-3. Interestingly, measures of ecological and perceived impact, such as the ESS and the VAS, showed similar improvements in both groups, indicating a non-specific effect of cognitive rehabilitation on the selfperceived impact of cognitive impairment.…”
Section: Multiple Sclerosis Msj Journalmentioning
confidence: 63%
“…The primary efficacy variable was responder status, defined as consistency of gait speed improvement (ie, gait speed for at least three of the four assessments during the treatment period greater than the functional electrical stimulation with or without exercise, 28,29,35 conventional physical therapy, [31][32][33][34][36][37][38] and other interventions, including whole-body vibration, [39][40][41] torso weighting, 42 Wii activities, 43,44 massage, 45 and rhythmic auditory stimulation. 46 Although many of these studies measured treatment effects on walking ability, [21][22][23][24][25][26][27][28]30,31,34,[36][37][38]42,46,47 this review focuses on only the task-specific gait training RCTs. [21][22][23][24][25][26] The individual study findings from the gait training RCTs (k = 6) are summarized in Table 2.…”
Section: Effects Of Dalfampridine On Gait Speed In Msmentioning
confidence: 99%